If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(p + -1) = 7 + p Reorder the terms: 2(-1 + p) = 7 + p (-1 * 2 + p * 2) = 7 + p (-2 + 2p) = 7 + p Solving -2 + 2p = 7 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -2 + 2p + -1p = 7 + p + -1p Combine like terms: 2p + -1p = 1p -2 + 1p = 7 + p + -1p Combine like terms: p + -1p = 0 -2 + 1p = 7 + 0 -2 + 1p = 7 Add '2' to each side of the equation. -2 + 2 + 1p = 7 + 2 Combine like terms: -2 + 2 = 0 0 + 1p = 7 + 2 1p = 7 + 2 Combine like terms: 7 + 2 = 9 1p = 9 Divide each side by '1'. p = 9 Simplifying p = 9
| c=14+1.4w | | x*2+8=30 | | 3x+14=-8-8 | | y-2.25=-5.75 | | 7*3x+2=16 | | t-6=4 | | x^2-x-12=o | | 3x+5=5(x-5) | | v=f(b+a) | | 3/4=6/n | | 2x+3=3(x-2) | | x-sqrx+11=1 | | m(m+10)=-34 | | 7x+6.2x+3.5=-25.54 | | 5/9=20/36 | | 9x-3y=20 | | 2/f-6=8 | | 7+5x-2x=16+2x-2x | | 7x+8-6x=14 | | 0.1(x-7)+0.05=0.8 | | 5f+3=28 | | y^2=4y-6 | | m=n+12 | | 20/2 | | 6w=54 | | W-54=6 | | W/6=54 | | -x^2+12x-27=0 | | 5(x-4)+6=2x+3(-3+x) | | S/6+8=13 | | 3x^2-3x=o | | 3p+65=7p+37 |